2010
DOI: 10.1016/s0929-6646(10)60100-3
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Hyalinizing Angiectatic Tumor of Soft Parts

Abstract: Pleomorphic hyalinizing angiectatic tumor (PHAT) of soft parts is a rare, nonmetastasizing tumor of uncertain lineage which was first reported in 1996. Here, we report a case of PHAT and review the literature. A 49-year-old man presented with a soft and progressively enlarging mass over the right buttock for several years. On suspicion that the mass was a right gluteal lipoma, he underwent surgical excision. The excised lesion measured 14 x 6 x 3.5 cm. It had a variegated appearance with a white-tan to yellowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…The tumor demarcation in the present case may be related to marked intratumoral hemorrhage, which may in turn be derived from vascular permeability induced by intratumoral mast‐cell products . Among the previously reported macroscopically demarcated PHATs, five were described as having a microscopic infiltrative border, but no satellite lesions were found. The pathogenesis of the satellite lesions remains unclear at present.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The tumor demarcation in the present case may be related to marked intratumoral hemorrhage, which may in turn be derived from vascular permeability induced by intratumoral mast‐cell products . Among the previously reported macroscopically demarcated PHATs, five were described as having a microscopic infiltrative border, but no satellite lesions were found. The pathogenesis of the satellite lesions remains unclear at present.…”
Section: Discussionmentioning
confidence: 54%
“…Smith et al reported that PHATs usually have an infiltrative margin, and Folpe and Weiss also demonstrated infiltrative growth in all cases of PHAT. However, further cases of demarcated PHAT have been reported, and among those in which the tumor's macroscopic appearance was described, 25 had an infiltrative margin and 16 had a demarcated margin. The tumor demarcation in the present case may be related to marked intratumoral hemorrhage, which may in turn be derived from vascular permeability induced by intratumoral mast‐cell products .…”
Section: Discussionmentioning
confidence: 99%
“…The disease was mainly found in the trunk, limbs and subcutaneous tissue of lower limbs in adult women. It generally appeared as a mass of slow growth (18). The histological features were thin-walled and expanded blood vessels that were distributed in clusters; the walls and matrix transparently degenerated and residual pleomorphic tumor was visible among blood vessels with the split as low as <1/50 HPF.…”
Section: Discussionmentioning
confidence: 99%
“…PHAT describes a heterogeneous group of neoplasms of undetermined tumorigenesis, characterized by clusters of ectatic, fibrinlined, and thin-walled vessels that are surrounded by spindled or pleomorphic neoplastic cells with variable inflammatory components. The neoplastic cells frequently have intracytoplasmic hemosiderin granules, intranuclear inclusions, and low mitotic activity [2][3][4][5]. Based only on the morphological findings of histopathology, the biological potential of the tumor is indeterminate.…”
Section: Introductionmentioning
confidence: 99%
“…The proliferative spindle cells of the neurofibroma and the intense inflammation associated with the granuloma were considered to have contributed to the increased FDG uptake (SUVm = 4.6 and 10.8, respectively) in those cases. Only one previous case of PHAT had been found at our institution [3], and that tumor had displayed mild FDG uptake (SUVm = 1.4) during FDG-PET examination. In PHAT, we propose that FDG accumulation in the ectatic vessel, increased uptake of the pleomorphic cells and/or associated inflammatory cells, and increased permeability of the stroma lead to the imaging feature.…”
mentioning
confidence: 95%